Transmission of MPEG-2 over non-guaranteed quality of service (QoS) network / Mohd Asraf Mohd Radzi - Mohd Radzi, Mohd Asraf (Faculty of Information Technology and Quantitative Sciences, 2005)
This day, multimedia is very important to the growth of the internet and networking. Multimedia transport was used to deliver the multimedia on the network. User like to use the streaming technology as the video is not save in the computer but the video is played from a server in the internet. There are a lot of video that can be stream on internet. But to search for a quality and suitable for the streaming purpose is very difficult. MPEG committee has developed many video formats and this day MPEG video format is one of the best quality as the video format is now being use for many commercial use such as broadband television, DVD video format and streaming itself. The mpeg2 video format is see as a good video format to deploy in streaming application.